A normative analysis of mandatory childhood vaccination for measles - Pillay, Subeshini (My University, 2021)
The arguments ‘for’ and ‘against’ compulsory childhood measles vaccinations have been a topic of interest recently following the multitude of measles outbreaks worldwide. While the large number of deaths accompanying these outbreaks is due to several reasons, vaccine hesitancy seems to be the biggest cause. Intentional failures to vaccinate stem predominantly from misinformation concerning the safety of measles vaccines and from religious convictions. The focus of this study is to determine whether it is ethically acceptable to restrict parental autonomy for the well being of the greater population. In other words, should childhood measles vaccination be mandatory? This is a purely normative study. The research method comprised a literature search on the primary sources and research articles on the causes of measles outbreaks and how they can be prevented were reviewed. From these sources I developed arguments in support of the thesis using ethical theories and legal principles. This research defends main arguments grounded on utilitarianism, Mill’s harm principle, ubuntu and John Rawls’ theory of justice that support mandatory vaccination. Firstly, the state should oblige parents to vaccinate their children to protect them and others from the harmful effects of measles. Secondly, the state should secure herd immunity as a public good by ensuring mass cooperation. By providing an analysis of multiple moral frameworks and addressing obvious objections, this report results and concludes in a normative argument for policy makers to implement mandatory childhood measles vaccination to increase levels of herd immunity, and eventually lead to the eradication of measles
A research report submitted in fulfilment of the requirements for the degree Masters of Science in Medicine (Bioethics and Health Law) to the Faculty of Health Sciences, School of Clinical Medicine, University of the Witwatersrand, Johannesburg, 2021